Pengaruh Penggunaan Media Flipbook terhadap Hasil Belajar Siswa Materi Hukum Permintaan dan Penawaran Kelas X SMA Negeri 2 Bondowoso - Nurida, Raniyah; Widodo, Joko; Herlindawati, Dwi (Education Journal : Journal Educational Research and Development, 2024)
This research aims to determine the effect of using flipbook media on student learning outcomes in material on the law of supply and demand for class X SMA Negeri 2 Bondowoso. The type of research used is a quasi-experimental design using a nonequivalent control group design. Sampling used purposive sampling in class X G as the control class and class X D as the experimental class. Data collection techniques are tests and interviews. Data analysis techniques are the Independent Sample t-test and the N-Gain test. The results of the research show that there is an influence of the use of flipbook media on student learning outcomes with a significant value of 0.000 ? 0.05 and the N-Gain test in the control class obtained an average value of 0.1 and the experimental class obtained an average value of 0.5. From this comparison it can be concluded that the experimental class had a higher increase in learning outcomes than the control class. Based on the N-Gain assessment criteria, the control class is included in the low criteria, namely Ngain ? 0.3, while the experimental class learning outcomes are included in the medium criteria, with a value of 0.3 ? N-Gain ? 0.70. This shows that implementing the use of flipbook media has a more significant influence on improving student learning outcomes compared to not implementing the use of flipbook media.